Our teacher likes you, so I like you: A social network approach to social referencing. (August 2017) - Hendrickx, Marloes M.H.G.; Mainhard, Tim; Boor-Klip, Henrike J.; Brekelmans, Mieke
Abstract: A teacher is a social referent for peer liking and disliking when students adjust their evaluations of a peer based on their perceptions of teacher liking and disliking for this peer. The present study investigated social referencing as an intra-individual process that occurs over time, using stochastic actor-oriented modeling with RSiena. The co-evolution of peer-perceived teacher liking and disliking networks with peer liking and disliking networks was analyzed in 52 fifth-grade classes in the Netherlands, with 1370 students ( M age  = 10.60). Results showed that when a student viewed the teacher to like a peer, this student would also like this peer. Regarding disliking, there was a stronger effect in the opposite direction, indicating that students' disliking a peer increased the likelihood that they would view the peer as disliked by the teacher as well. In sum, partial evidence for social referencing as an intra-individual process was found. For teachers this implies that the cues they provide regarding their liking of a student, and not necessarily their disliking, may affect individual peers' liking of this student.